Polycarbonate film with long-acting antistatic performance and preparation method thereof
A polycarbonate film with silicon-containing carbon dioxide-based polycarbonate and additives ensures long-lasting antistatic performance and improved flame retardancy by evenly distributing antistatic agents, addressing instability issues and enhancing mechanical strength.
Patent Information
- Application Number
- CN202411611627.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polycarbonate films suffer from unstable antistatic properties due to the degradation of antistatic agents over time, leading to reduced effectiveness in static charge dissipation and potential harm to electronic equipment and personnel, and are affected by environmental conditions.
A polycarbonate film formulation incorporating silicon-containing carbon dioxide-based polycarbonate, an antistatic agent, auxiliary flame retardant, antioxidant, and coupling agent, prepared through specific polymerization and mixing processes to ensure long-lasting antistatic performance.
The film maintains stable antistatic properties over time, enhances flame retardancy, and improves mechanical strength by evenly distributing antistatic agents within the film matrix, ensuring consistent charge dissipation and resistance to static accumulation.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of films, and in particular to a polycarbonate film with long-lasting antistatic performance and a preparation method thereof. Background Art
[0002] Polycarbonate film is a high-performance material made of polycarbonate resin. Polycarbonate film is one of the five general engineering plastics and has many excellent properties. Polycarbonate film can also be added with various functional ingredients to obtain flame retardant, antistatic, conductive, fluorescent, diffusion and other functions.
[0003] Polycarbonate film has good mechanical properties, electrical properties and heat resistance, making it an important material in the field of electronics and electrical appliances. Polycarbonate film can be used to make insulation materials, display and control panels, touch screens, LED lights, etc.
[0004] Although polycarbonate film has excellent properties in many aspects, it still has some disadvantages in antistatic properties. Polycarbonate film is prone to static electricity during friction or contact. The accumulation of static electricity not only affects the use effect of the film, but may also cause harm to surrounding electronic equipment and personnel. The antistatic performance of polycarbonate film is affected by many factors, such as temperature, humidity, surface treatment, etc. Under different conditions, the antistatic performance of the film may change, resulting in unstable use effect. For example, under high temperature or dry environment, the antistatic performance of the film may decrease; under humid environment, the antistatic performance of the film may increase. This instability limits the application of polycarbonate film in certain specific environments.
[0005] The antistatic properties of polycarbonate films may decrease over time. This is mainly due to the gradual loss or decomposition of the antistatic agent in the film. The poor durability of the antistatic properties may cause the polycarbonate film to lose its antistatic function during long-term use, thus affecting its use effect. Summary of the invention
[0006] In order to overcome the deficiencies of the prior art, the present invention provides a polycarbonate film with long-term antistatic performance and a preparation method thereof. An antistatic agent is added to the film. The presence of the antistatic agent can reduce the accumulation of static electricity on the surface of the film, thereby preventing the adverse effects of static electricity. Moreover, by reasonably mixing silicon-containing carbon dioxide-based polycarbonate, antistatic agent, auxiliary flame retardant, antioxidant and coupling agent, the film is ensured to have good antistatic performance, high flame retardancy and good anti-oxidative tear strength.
[0007] The technical solution adopted by the present invention to solve its technical problem is: The first object of the present application is to provide a polycarbonate film with long-lasting antistatic properties, which comprises the following raw materials in parts by weight: 100-200 parts of silicon-containing carbon dioxide-based polycarbonate, 10-20 parts of antistatic agent, 8-15 parts of auxiliary flame retardant, 3-5 parts of antioxidant, 3-5 parts of coupling agent; The preparation method of silicon-containing carbon dioxide-based polycarbonate comprises the following steps: (1) Adding monomers, catalysts and co-catalysts into a pre-dried autoclave; The materials are added in a ratio of monomer: catalyst: co-catalyst = 1000:1:1; the monomer is composed of 10% 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 90% propylene oxide in terms of weight percentage; (2) charging CO2 into the autoclave of step (1) until the pressure in the autoclave reaches 3 MPa; reacting for 6 hours at 25°C and stirring at 200 rpm to obtain a polymer; (3) The polymer is dissolved in a dichloromethane solution, and then ethanol is added to remove impurities to obtain a purified polymer; the purified polymer is placed in a vacuum drying oven and dried at 60° C. for 48 hours to obtain a silicon-containing carbon dioxide-based polycarbonate for later use.
[0008] In one or more technical solutions, the polycarbonate film comprises the following raw materials in parts by weight: 130-190 parts of silicon-containing carbon dioxide-based polycarbonate, 12-18 parts of antistatic agent, 10-13 parts of auxiliary flame retardant, 3-5 parts of antioxidant, and 3-5 parts of coupling agent.
[0009] In one or more technical solutions, the polycarbonate film comprises the following raw materials in parts by weight: 150 parts of silicon-containing carbon dioxide-based polycarbonate, 15 parts of antistatic agent, 12 parts of auxiliary flame retardant, 4 parts of antioxidant, and 4 parts of coupling agent.
[0010] In one or more technical solutions, the method for preparing the antistatic agent comprises the following steps: (1) In a nitrogen atmosphere, anhydrous ethanol, methacryloyloxyethyl trimethyl ammonium chloride, styrene and hydroxyethyl methacrylate are added into a reactor to obtain a mixed solution; wherein the molar ratio of methacryloyloxyethyl trimethyl ammonium chloride, styrene and hydroxyethyl methacrylate is 2:1:1; (2) adding an initiator to the mixed solution of step (1), slowly raising the temperature to 75°C, and reacting at 75°C for 6 hours; (3) After the reaction in step (3) is completed, the ethanol is removed by concentration to obtain a concentrated solution; (4) The concentrated solution was added dropwise into toluene for precipitation, and then dried in a vacuum drying oven at 80° C. for 24 hours to obtain an antistatic agent.
[0011] In one or more technical solutions, the initiator is azobisisobutyronitrile.
[0012] In one or more technical solutions, the molar ratio of methacryloyloxyethyltrimethylammonium chloride to azobisisobutyronitrile is 100:2.4-2.5.
[0013] In one or more technical solutions, the auxiliary flame retardant is bisphenol A bis(diphenyl) phosphate.
[0014] In one or more technical solutions, the antioxidant is di-tert-butyl-p-cresol.
[0015] In one or more technical solutions, the coupling agent is 3-acryloxypropyltrimethoxysilane.
[0016] The second object of the present application is to provide a method for preparing the polycarbonate film with long-lasting antistatic properties, comprising the following steps: S1. Preparation of Silicon-Containing Carbon Dioxide-Based Polycarbonate (1) Adding monomers, catalysts and co-catalysts into a pre-dried autoclave; The materials are added in a ratio of monomer: catalyst: co-catalyst = 1000:1:1; the monomer is composed of 10% 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 90% propylene oxide in terms of weight percentage; (2) charging CO2 into the autoclave of step (1) until the pressure in the autoclave reaches 3 MPa; reacting for 6 hours at 25°C and stirring at 200 rpm to obtain a polymer; (3) dissolving the polymer in a dichloromethane solution, and then adding ethanol to remove impurities to obtain a purified polymer; placing the purified polymer in a vacuum drying oven at 60° C. for 48 hours to obtain a silicon-containing carbon dioxide-based polycarbonate for later use; S2. Preparation of antistatic agent (1) In a nitrogen atmosphere, anhydrous ethanol, methacryloyloxyethyl trimethyl ammonium chloride, styrene and hydroxyethyl methacrylate are added into a reactor to obtain a mixed solution; wherein the molar ratio of methacryloyloxyethyl trimethyl ammonium chloride, styrene and hydroxyethyl methacrylate is 2:1:1; (2) adding an initiator to the mixed solution of step (1), slowly raising the temperature to 75°C, and reacting at 75°C for 6 hours; (3) After the reaction in step (2) is completed, the ethanol is removed by concentration to obtain a concentrated solution; (4) adding the concentrated solution dropwise into toluene for precipitation, and then drying in a vacuum drying oven at 80° C. for 24 hours to obtain an antistatic agent; S3. Film forming process According to the weight composition of each raw material of the polycarbonate film, the corresponding weight parts of silicon-containing carbon dioxide-based polycarbonate, antistatic agent, auxiliary flame retardant, and antioxidant are fully mixed; the mixed raw materials are extruded and granulated at a temperature of 180-190° C. using a twin-screw extruder; the granulated material is cast at a temperature of 170-175° C. by a casting machine to form a film sheet; The cast film sheet was stretched at a stretching temperature of 165° C. to obtain a polycarbonate film.
[0017] The beneficial effects of the present invention are: 1. The polycarbonate film described in the present application, the silicon-containing carbon dioxide-based polycarbonate can improve the thermal stability and mechanical properties of the film by introducing silicon-containing groups. The silicon-containing carbon dioxide-based polycarbonate, as the base material of the film, provides a basis for the uniform dispersion and stable existence of the antistatic agent. Through the synergistic effect with the antistatic agent, the film can maintain antistatic properties for a long time.
[0018] 2. The polycarbonate film described in the present application has a stable ammonium cation on the antistatic agent molecular chain, which can increase the charge density of the polymer and promote the transfer of charge. At the same time, a styrene component is introduced into the antistatic agent molecule to improve the compatibility with the silicon-containing carbon dioxide-based polycarbonate, and hydroxyethyl methacrylate is used as a hydrophilic component to enhance the hygroscopicity of the copolymer, so that the antistatic agent can be effectively dispersed in the polycarbonate film and can quickly conduct and dissipate static charge.
[0019] During the preparation process, the antistatic agent is fully mixed with silicon-containing carbon dioxide-based polycarbonate and the like and extruded and cast into a film; the antistatic agent molecules can be evenly distributed on the inner and outer surfaces of the film to form a continuous antistatic layer. When the antistatic agent molecules on the surface of the film are lost due to water washing or friction, the antistatic agent molecules inside can migrate to the surface for replenishment due to the difference in concentration gradient, thereby maintaining the antistatic effect for a longer period of time.
[0020] 3. The polycarbonate film described in the present application can effectively improve the flame retardant properties of the polycarbonate film by adding an antistatic agent and a flame retardant at the same time. DETAILED DESCRIPTION
[0021] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.
[0022] Preparation Example 1 The preparation method of silicon-containing carbon dioxide-based polycarbonate comprises the following steps: (1) Adding monomers, catalysts and co-catalysts to a pre-dried autoclave; wherein the monomers are added in a ratio of monomer:catalyst:co-catalyst = 1000:1:1; the monomers are composed of 10% by weight of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 90% by weight of propylene oxide; in this preparation example, 1 mol of the monomer is used; (2) charging CO2 into the autoclave in step (1) until the pressure in the autoclave reaches 3 MPa; reacting for 6 hours at 25°C and stirring at 200 rpm to obtain a polymer; (3) The polymer of step (2) is dissolved in 5 volumes of dichloromethane solution, and then 10 volumes of ethanol are added to remove cyclic byproducts, catalysts and low molecular weight polymers to obtain a purified polymer; the purified polymer is placed in a vacuum drying oven at 60° C. and dried for 48 hours to obtain a silicon-containing carbon dioxide-based polycarbonate for standby use.
[0023] The chemical reaction process involved in preparing silicon-containing carbon dioxide-based polycarbonate is as follows:
[0024] Through a universal testing machine, at room temperature 20°C, 30% RH, and a tensile rate of 5 mm min -1 The silicon-containing carbon dioxide-based polycarbonate was tested under the conditions of , and the tensile strength reached 34.5MPa, and the elongation at break was 11.6%. This shows that the silicon-containing carbon dioxide-based polycarbonate has high strength and certain toughness.
[0025] Using Fourier transform infrared spectroscopy, it was found that the absorption peak of carbonyl (C=O) appeared at 1750 cm -1 The absorption peak of the Si-O bond on the side chain appears at 1090 cm -1 The existence of these characteristic absorption peaks proves the successful synthesis of polycarbonate and the presence of methoxysilyl groups in the side chains.
[0026] Preparation Example 2 The preparation method of the antistatic agent comprises the following steps: (1) In a nitrogen atmosphere, anhydrous ethanol, methacryloyloxyethyl trimethyl ammonium chloride, styrene and hydroxyethyl methacrylate are added into a reactor, and stirred at a speed of 200 rpm at room temperature to obtain a mixed solution; wherein the molar ratio of methacryloyloxyethyl trimethyl ammonium chloride, styrene and hydroxyethyl methacrylate is 2:1:1; (2) Add an initiator to the mixed solution, slowly raise the temperature to 75°C, and react at 75°C for 6 hours to obtain a quaternary ammonium salt antistatic agent.
[0027] (3) After the reaction in step (2) is completed, the ethanol is removed by concentration to obtain a concentrated solution; (4) The concentrated solution was added dropwise into toluene for precipitation, and then dried in a vacuum drying oven at 80° C. for 24 hours to obtain a quaternary ammonium salt antistatic agent.
[0028] The chemical reaction process involved in the preparation of antistatic agents is as follows: Among them, y:x:z in the quaternary ammonium salt antistatic agent is 10:5:5.
[0029] Using Fourier infrared spectroscopy, it was found that at 1725 cm -1 The absorption peak of C=O appears at 1145 cm -1 The peaks at 1454 cm-1 are the stretching vibration peaks of COC, which can confirm the presence of ester structures in the antistatic agent. -1 The cationic group -CH2-N + The bending vibration absorption peak of the methylene group is 952 cm -1 -CH2-N + The characteristic absorption peak of methyl in (CH3)3 is 1388cm -1 The -CH3 stretching vibration peak at 1490 cm -1 The benzene ring skeleton vibration peak appears at 701 cm -1 There is a strong absorption peak at , which comes from the -CH bending vibration of monosubstituted benzene, proving the presence of styrene units in the polymer.
[0030] Example 1 A polycarbonate film with long-lasting antistatic properties, comprising the following raw materials in parts by weight: 100 parts of silicon-containing carbon dioxide-based polycarbonate (from Preparation Example 1), 10 parts of antistatic agent (from Preparation Example 2), 8 parts of bisphenol A bis(diphenyl) phosphate, 3 parts of di-tert-butyl-p-cresol, and 3 parts of 3-acryloxypropyltrimethoxysilane; The preparation method of silicon-containing carbon dioxide-based polycarbonate comprises the following steps: Put silicon-containing carbon dioxide-based polycarbonate, antistatic agent, auxiliary flame retardant, and antioxidant into a vacuum drying oven, dry at 60° C. for 24 hours for use; fully mix the silicon-containing carbon dioxide-based polycarbonate, antistatic agent, auxiliary flame retardant, and antioxidant in corresponding weight parts according to the weight parts of each raw material of the polycarbonate film; extrude and granulate the mixed raw materials at a temperature of 190° C. using a twin-screw extruder; and cast the granulated materials at a temperature of 175° C. through a casting machine to form a film sheet; The cast film sheet was stretched at a stretching temperature of 165° C. (stretching ratio of 3 times) to obtain a polycarbonate film with a thickness of 20±1 μm.
[0031] Example 2 A polycarbonate film with long-lasting antistatic properties, comprising the following raw materials in parts by weight: 150 parts of silicon-containing carbon dioxide-based polycarbonate (from Preparation Example 1), 15 parts of antistatic agent (from Preparation Example 2), 12 parts of bisphenol A bis(diphenyl) phosphate, 4 parts of di-tert-butyl-p-cresol, and 4 parts of 3-acryloxypropyltrimethoxysilane; The remaining conditions are the same as those in Example 1.
[0032] Example 3 A polycarbonate film with long-lasting antistatic properties, comprising the following raw materials in parts by weight: 200 parts of silicon-containing carbon dioxide-based polycarbonate (from Preparation Example 1), 20 parts of antistatic agent (from Preparation Example 2), 15 parts of bisphenol A bis(diphenyl) phosphate, 5 parts of di-tert-butyl-p-cresol, and 5 parts of 3-acryloxypropyltrimethoxysilane; The remaining conditions are the same as those in Example 1.
[0033] Example 4 A polycarbonate film with long-lasting antistatic properties, comprising the following raw materials in parts by weight: 130 parts of silicon-containing carbon dioxide-based polycarbonate (from Preparation Example 1), 12 parts of antistatic agent (from Preparation Example 2), 10 parts of bisphenol A bis(diphenyl) phosphate, 3 parts of di-tert-butyl-p-cresol, and 3 parts of 3-acryloxypropyltrimethoxysilane; The remaining conditions are the same as those in Example 1.
[0034] Example 5 A polycarbonate film with long-lasting antistatic properties, comprising the following raw materials in parts by weight: 190 parts of silicon-containing carbon dioxide-based polycarbonate (from Preparation Example 1), 18 parts of antistatic agent (from Preparation Example 2), 13 parts of bisphenol A bis(diphenyl) phosphate, 4 parts of di-tert-butyl-p-cresol, and 5 parts of 3-acryloxypropyltrimethoxysilane; The remaining conditions are the same as those in Example 1.
[0035] Comparative Example 1 Polycarbonate film, in parts by weight, comprises the following materials: 100 parts of silicon-containing carbon dioxide-based polycarbonate (from Preparation Example 1); The remaining conditions are the same as those in Example 1.
[0036] Comparative Example 2 Polycarbonate film, in parts by weight, comprises the following materials: 100 parts of silicon-containing carbon dioxide-based polycarbonate (from Preparation Example 1), 8 parts of bisphenol A bis(diphenyl)phosphate, 3 parts of di-tert-butyl-p-cresol, and 3 parts of 3-acryloxypropyltrimethoxysilane; The remaining conditions are the same as those in Example 1.
[0037] Comparative Example 3 Polycarbonate film, in parts by weight, comprises the following materials: 100 parts of silicon-containing carbon dioxide-based polycarbonate (from Preparation Example 1), 10 parts of antistatic agent (from Preparation Example 2), 3 parts of di-tert-butyl-p-cresol, and 3 parts of 3-acryloxypropyltrimethoxysilane; The remaining conditions are the same as those in Example 1.
[0038] Comparative Example 4 Polycarbonate film, in parts by weight, comprises the following materials: 100 parts of silicon-containing carbon dioxide-based polycarbonate (from Preparation Example 1), 10 parts of antistatic agent (from Preparation Example 2), 8 parts of bisphenol A bis(diphenyl) phosphate, and 3 parts of di-tert-butyl-p-cresol; The remaining conditions are the same as those in Example 1.
[0039] The polycarbonate films prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to the following performance tests, and the test results are summarized in Table 1.
[0040] 1. Normal antistatic testing: According to GB / T 31838.3-2019, the surface resistivity of the sample to be tested is measured in a specific environment (temperature 23°C, relative humidity 50%) using a high resistance meter, and the test voltage is set to 500 V; before the test, the sample to be tested is placed in an environment of 23°C and relative humidity 50% for 24 hours.
[0041] 2. Long-term antistatic testing Rinse and wipe the sample with distilled water for 10 minutes, then place it in a vacuum drying oven and dry it at 80°C for 2 hours. Place the sample in an environment of 80°C and 10% relative humidity for 24*6 hours, and then test the surface resistivity of the sample.
[0042] 3. Flame retardancy test Tested and judged according to UL94 vertical burning.
[0043] 4. Tear strength test The test was carried out according to the method of standard GB / T 16578.2-2009.
[0044] Table 1 From Table 1, we can see that: The films prepared in Example 1-5 have good antistatic properties and a surface resistivity of 10 15 Within the Ω level range; The long-term antistatic performance is also excellent, and the surface resistivity remains at 10 after treatment. 15 Ω level; The flame retardant grade is V-0, indicating that it has very good flame retardant properties; The tear strength is between 5.48 and 5.74 N / mm, showing good mechanical strength.
[0045] The film of Comparative Example 1 contains only silicon-containing carbon dioxide-based polycarbonate, but does not contain other ingredients such as antistatic agent, auxiliary flame retardant, antioxidant and coupling agent. Its properties are as follows: Normal antistatic: surface resistivity is 5.5×10 3 Ω; Long-term antistatic: surface resistivity is 2.5×10 2 Ω; Flame retardant grade is V-2, and the flame retardant performance is poor. Tear strength: 5.31 N / mm.
[0046] Compared with Example 1, Comparative Example 1 lacks antistatic agents and other additives, so its antistatic performance is significantly poorer. The role of the antistatic agent is to form a layer of material on the surface of the film that can quickly dissipate the charge, thereby reducing the accumulation of static electricity. Since no antistatic agent is added to Comparative Example 1, its surface is more likely to accumulate static electricity, resulting in a lower surface resistivity. In addition, Comparative Example 1 did not show good flame retardancy in the flame retardant test, which may also be due to the lack of auxiliary flame retardants. Although the main function of antioxidants and coupling agents is not to improve antistatic properties, they also play an important role in improving the overall stability and performance of the material.
[0047] The film of Comparative Example 2 includes silicon-containing carbon dioxide-based polycarbonate, bisphenol A bis(diphenyl) phosphate, di-tert-butyl-p-cresol and 3-acryloxypropyltrimethoxysilane, but no antistatic agent is added. From Table 1, we can see that: Normal antistatic: surface resistivity is 3.7×10 4 Ω; Long-term antistatic: surface resistivity is 5.8×10 3 Ω; Flame retardant grade: V-1; Tear strength: 5.35 N / mm.
[0048] Comparative Example 2 has poor antistatic performance because it lacks an antistatic agent. Antistatic agents help reduce static electricity accumulation on the film surface, and since Comparative Example 2 does not have this ingredient, its antistatic ability is significantly lower than that of Example 1 containing an antistatic agent. In addition, the flame retardant grade of Comparative Example 2 is V-1, which indicates that its flame retardant performance is slightly lower than the V-0 grade of Example 1, but still has certain flame retardancy. In terms of tear strength, Comparative Example 2 is not much different from Example 1, indicating that even without an antistatic agent, the basic physical properties of the film, such as tear strength, are slightly affected.
[0049] The film of Comparative Example 3 includes silicon-containing carbon dioxide-based polycarbonate, an antistatic agent, di-tert-butyl-p-cresol and 3-acryloxypropyltrimethoxysilane, but does not include an auxiliary flame retardant. Its properties are as follows: Normal antistatic: surface resistivity is 1.7×10 14 Ω; Long-term antistatic: surface resistivity is 1.4×10 14 Ω; Flame retardant grade: V-1; Tear strength: 5.41 N / mm.
[0050] Compared with Example 1, although both Comparative Example 3 and Example 1 have antistatic agents, Comparative Example 3 lacks auxiliary flame retardant, which leads to a lower flame retardancy.
[0051] The polycarbonate film of Comparative Example 4 has normal antistatic properties: the surface resistivity is 0.8×10 13 Ω; Long-term antistatic performance: surface resistivity is 1.2×10 12 Ω; Flame retardant grade: V-0; Tear strength: 5.36 N / mm.
[0052] Compared with Example 1, Comparative Example 4 lacks a coupling agent (3-acryloxypropyltrimethoxysilane). Coupling agents are usually used to improve the compatibility and bonding between components within the material, which is very important for ensuring the overall performance of the film, especially the antistatic performance and mechanical properties. Therefore, although Comparative Example 4 also contains an antistatic agent, due to the lack of a coupling agent, the antistatic agent is not evenly dispersed in the polycarbonate matrix or is not firmly bonded to the matrix, resulting in a decrease in antistatic performance. In addition, although the antistatic performance of Comparative Example 4 is not as good as that of Example 1, the flame retardant performance and tear strength are still maintained at a relatively high level, which indicates that other added ingredients such as bisphenol A bis (diphenyl) phosphate and di-tert-butyl-p-cresol play a role in these performance indicators.
[0053] Through comparative analysis of Examples 1, 2, 3, 4 and Example 1, it can be seen that the following raw materials have a synergistic effect in the long-term antistatic performance, flame retardant performance and mechanical strength of the polycarbonate film: Antistatic agent: The antistatic properties of Comparative Examples 1 and 2 are significantly lower than that of Example 1, because Comparative Example 1 does not contain an antistatic agent, while Comparative Example 2, although containing an auxiliary flame retardant, an antioxidant and a coupling agent, also lacks an antistatic agent. This indicates that the antistatic agent plays a key role in reducing static electricity accumulation on the film surface.
[0054] Auxiliary flame retardant: The flame retardancy levels of Comparative Examples 1 and 3 are V-2 and V-1 respectively, while the flame retardancy level of Example 1 is V-0. Comparative Example 1 does not add auxiliary flame retardant, and Comparative Example 3 has an antistatic agent but lacks auxiliary flame retardant, which shows that auxiliary flame retardant is important for improving the flame retardancy of the film.
[0055] Antioxidants and coupling agents: Although the main function of antioxidants and coupling agents is not to improve antistatic properties, the comparison of the tear strength between Comparative Example 1 and Example 1 shows that the addition of antioxidants and coupling agents helps to improve the overall stability and mechanical strength of the film. Comparative Example 1 does not contain antioxidants and coupling agents, and its tear strength is 5.31 N / mm, while the tear strength of Example 1 is 5.48 N / mm, indicating that antioxidants and coupling agents contribute to improving the overall performance of the material.
[0056] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A polycarbonate film having long-lasting antistatic properties, characterized in that: In parts by weight, it includes the following raw materials: 100-200 parts of silicon-containing carbon dioxide-based polycarbonate, 10-20 parts of antistatic agent, 8-15 parts of auxiliary flame retardant, 3-5 parts of antioxidant, 3-5 parts of coupling agent; The preparation method of silicon-containing carbon dioxide-based polycarbonate comprises the following steps: (1) Adding monomers, catalysts and co-catalysts into a pre-dried autoclave; The materials are added in a ratio of monomer: catalyst: co-catalyst = 1000:1:1; the monomer is composed of 10% 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 90% propylene oxide in terms of weight percentage; (2) charging CO2 into the autoclave of step (1) until the pressure in the autoclave reaches 3 MPa; reacting for 6 hours at 25°C and stirring at 200 rpm to obtain a polymer; (3) The polymer is dissolved in a dichloromethane solution, and then ethanol is added to remove impurities to obtain a purified polymer; the purified polymer is placed in a vacuum drying oven and dried at 60° C. for 48 hours to obtain a silicon-containing carbon dioxide-based polycarbonate for later use.
2. The polycarbonate film according to claim 1, characterized in that In parts by weight, it includes the following raw materials: 130-190 parts of silicon-containing carbon dioxide-based polycarbonate, 12-18 parts of antistatic agent, 10-13 parts of auxiliary flame retardant, 3-5 parts of antioxidant, and 3-5 parts of coupling agent.
3. The polycarbonate film according to claim 1, characterized in that In parts by weight, it includes the following raw materials: 150 parts of silicon-containing carbon dioxide-based polycarbonate, 15 parts of antistatic agent, 12 parts of auxiliary flame retardant, 4 parts of antioxidant, and 4 parts of coupling agent.
4. The polycarbonate film according to claim 1, characterized in that The preparation method of the antistatic agent comprises the following steps: (1) In a nitrogen atmosphere, anhydrous ethanol, methacryloyloxyethyl trimethyl ammonium chloride, styrene and hydroxyethyl methacrylate are added into a reactor to obtain a mixed solution; wherein the molar ratio of methacryloyloxyethyl trimethyl ammonium chloride, styrene and hydroxyethyl methacrylate is 2:1:1; (2) adding an initiator to the mixed solution of step (1), slowly raising the temperature to 75°C, and reacting at 75°C for 6 hours; (3) After the reaction in step (3) is completed, the ethanol is removed by concentration to obtain a concentrated solution; (4) The concentrated solution was added dropwise into toluene for precipitation, and then dried in a vacuum drying oven at 80° C. for 24 hours to obtain an antistatic agent.
5. The polycarbonate film according to claim 4, characterized in that The initiator is azobisisobutyronitrile.
6. The polycarbonate film according to claim 4, characterized in that The molar ratio of the methacryloyloxyethyl trimethylammonium chloride to azobisisobutyronitrile is 100:2.4-2.
5.
7. The polycarbonate film according to claim 1, characterized in that The auxiliary flame retardant is bisphenol A bis(diphenyl) phosphate.
8. The polycarbonate film according to claim 1, characterized in that The antioxidant is di-tert-butyl-p-cresol.
9. The polycarbonate film according to claim 1, characterized in that The coupling agent is 3-acryloxypropyltrimethoxysilane.
10. The method for preparing a polycarbonate film with long-lasting antistatic properties according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Preparation of Silicon-Containing Carbon Dioxide-Based Polycarbonate S11. Adding monomers, catalysts and co-catalysts to a pre-dried autoclave; The materials are added in a ratio of monomer: catalyst: co-catalyst = 1000:1:1; the monomer is composed of 10% 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and 90% propylene oxide in terms of weight percentage; S12. The autoclave of step S11 was charged with CO2 until the pressure in the autoclave reached 3 MPa; the reaction was carried out at 25°C and a stirring speed of 200 rpm for 6 hours to obtain a polymer; S13. The polymer of step S12 is dissolved in a dichloromethane solution, and then ethanol is added to remove impurities to obtain a purified polymer; the purified polymer is placed in a vacuum drying oven at 60° C. and dried for 48 hours to obtain a silicon-containing carbon dioxide-based polycarbonate for standby use; S2. Preparation of antistatic agent S21. In a nitrogen atmosphere, anhydrous ethanol, methacryloyloxyethyl trimethyl ammonium chloride, styrene and hydroxyethyl methacrylate were added to a reactor to obtain a mixed solution; wherein the molar ratio of methacryloyloxyethyl trimethyl ammonium chloride, styrene and hydroxyethyl methacrylate was 2:1:1; S22. Add an initiator to the mixed solution of step S21, slowly raise the temperature to 75°C, and react at 75°C for 6 hours; S23. After the reaction in step S22 is completed, ethanol is removed by concentration to obtain a concentrated solution; S24. The concentrated solution of step S23 is added dropwise to toluene for precipitation, and then dried in a vacuum drying oven at 80° C. for 24 hours to obtain an antistatic agent; S3. Film forming process According to the weight composition of each raw material of the polycarbonate film, the corresponding weight parts of silicon-containing carbon dioxide-based polycarbonate, antistatic agent, auxiliary flame retardant, and antioxidant are fully mixed; the mixed raw materials are extruded and granulated using a twin-screw extruder; the granulated material is cast through a casting machine to form a film sheet; The cast film sheet is stretched to obtain a polycarbonate film.
Citation Information
Patent Citations
Permanent antistatic molding composition and preparation method thereof
CN101987897A
Halogen-free flame retardant antistatic PC / ABS alloy material and preparation method thereof
CN102585469A
High-strength antistatic transparent polycarbonate film and preparing method thereof
CN105504758A
High-content glass fiber reinforced antistatic PC composite material and preparation method thereof
CN106633778A
Transparent anti-scratch and anti-static flame-retarding polycarbonate composite material
CN107163537A
Cited By
Flame-retardant anti-static composite pearl wool material and preparation method thereof
CN121021957A